THE INFLUENCE OF EXPERIENTIAL MARKETING AND PERCEIVED VALUE ON SPOTIFY PREMIUM SUBSCRIPTION DECISIONS - Tindatu, Chintya Julia; Saerang, David Paul Elia; Tumiwa, Johan Reineer (Universitas Sam Ratulangi, 2025)
As music streaming becomes an integral part of daily life, Spotify stands out by offering both free and premium services. While Premium provides ad-free listening, offline downloads, and higher audio quality, many users still choose the free version. This study examines how experiential marketing and perceived value influence the decision of Generation Z in Manado to subscribe to Spotify Premium. Using a quantitative approach, data were collected from 102 respondents through questionnaires and analyzed with multiple linear regression. The results show that both experiential marketing and perceived value have a positive impact, individually and simultaneously, on purchase decisions. These findings emphasize that memorable user experiences and strong perceived benefits encourage Generation Z to upgrade from free to premium services. This research contributes to the understanding of digital subscription behavior and provides practical insights for companies in developing effective marketing strategies. Keywords: Experiential Marketing, Perceived Value, Purchase Decision